Significance of acanthosis nigricans in childhood obesity - BEREKET, ABDULLAH; DEMİRCİOĞLU, SERAP; GÜRAN, TÜLAY (WILEY-BLACKWELL, 2008)
Aim: Acanthosis nigricans (AN) is among the most common dermatologic manifestations of obesity and hyperinsulinism. In this study, we aimed to find the clinical and laboratory differences in obese children with AN and without AN (non-AN). Methods: In total, 160 obese children were included in the study. The duration of obesity, body mass index (BMI), BMI z-scores, birth weight, parental BMI, lipid profile, fasting and post-meal (PM) glucose and insulin levels were compared in 67 obese with AN and 93 obese without AN. Results: Age was similar in both groups. AN group had higher male to female ratio (42/25 in AN, 43/50 in non-AN; P = 0.03), higher BMI (30.3 +/- 6.1 in AN, 26.4 +/- 3.6 in non-AN; P < 0.001) and weight for height (162.6 +/- 28.8 in AN, 144.6 +/- 15.8 in non-AN; P < 0.001) than non-AN group. There were no significant differences between the groups in birth weight, parental BMI and blood pressure. AN group had higher fasting (19.9 +/- 16.2 mU/L in AN, 10.4 +/- 7.6 mU/L in non-AN; P < 0.001) and PM insulin (88.6 +/- 87.3 mU/L in AN, 51.1 +/- 42.0 mU/L in non-AN; P = 0.01) and homeostasis model assessment for insulin resistance (HOMA-IR) (4.0 +/- 2.5 in AN, 2.2 +/- 1.8 in non-AN; P < 0.001) than non-AN group. However, fasting and PM glucose, triglyceride, low-density lipoprotein-, high-density lipoprotein- and total cholesterol levels were similar in both groups. BMI was correlated with HOMA-IR in both groups (r = 0.40 for AN, r = 0.28 for non-AN). PM glucose and PM insulin were correlated in both groups (r = 0.56 for AN, r = 0.39 for non-AN). However, fasting glucose and fasting insulin were correlated in only non-AN (r = 0.25), but not in AN group. Conclusions: Obese children with AN show higher insulin levels and HOMA-IR. AN is an important predictor of the insulin resistance in childhood obesity. Insulin secretory dynamics seem to be disrupted in fasting state initially, which is reflected as the loss of fasting insulin-glucose correlation in AN group.
Keywords: acanthosis nigricans; childhood; insulin resistance; obesity; INSULIN-RESISTANCE; DIABETES RISK; CHILDREN; ADOLESCENTS; PREVALENCE; AMERICAN; MARKER